2007
DOI: 10.3102/0002831207308637
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neighborhood Context on the College Aspirations of African American Adolescents

Abstract: Previous research on educational aspirations has focused almost exclusively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 69 publications
(147 reference statements)
5
60
1
3
Order By: Relevance
“…This contradicts work from the US and New Zealand which suggests that a greater connectedness with school and peers, has a positive effect on aspiration and achievement (Andermann, 2002;Goodenow, 1993;Crespo et al, 2013). Adolescents in US schools who perceive themselves to be good students are: committed to school, attached to teachers, and have high college aspirations (Stewart et al, 2007). This begs the question, what is it about state schools in the UK that is different?…”
Section: Running Head: the Aspirations Of Adolescents From Areas Of Dcontrasting
confidence: 44%
See 1 more Smart Citation
“…This contradicts work from the US and New Zealand which suggests that a greater connectedness with school and peers, has a positive effect on aspiration and achievement (Andermann, 2002;Goodenow, 1993;Crespo et al, 2013). Adolescents in US schools who perceive themselves to be good students are: committed to school, attached to teachers, and have high college aspirations (Stewart et al, 2007). This begs the question, what is it about state schools in the UK that is different?…”
Section: Running Head: the Aspirations Of Adolescents From Areas Of Dcontrasting
confidence: 44%
“…Forming close relationships with teachers and other members of the school community has been found to have a protective effect, often leading to higher educational aspiration and performance (Anderman, 2002;Goodenow, 1993;Crespo, Jose, Kielpikowski & Prior, 2013;Stewart, Stewart & Simons, 2007). Research from the USA reported that discussions with adolescents about future plans among parents and teachers were found to be strongly related to positive academic outcomes (Epstein & Sanders, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the strength of this research thread, with its emphasis on pupils' current experiences as well as future life-worlds, has lead very few geographers to engage in studies of young people's aspirations in the manner that researchers in education studies have done (Cooper, 2009;Strand & Winston, 2008), teasing out the importance of schooling, parental influence and neighbourhood effects on pupils' educational and employment ambitions (Crozier, 2009;Stewart et al, 2007). Bauder's (2001: 605) research on the education and career advice given by community-based organisations in an urban US context is perhaps an exception to this trend.…”
Section: Geographies Of Education and Aspirationmentioning
confidence: 99%
“…These variables have been identified most pertinent which influence students' decision of going for higher education after going through a rigorous literature review (St. John & Somers, 1993;Valadez, 1998;Thayer, 2000;Choy, 2001;Gandara, 2001;Samarge, 2006;Stewart, Stewart, & Simons, 2007;Conley, 2008;Jenkins, Miyazaki, & Janosik, 2009). The present study employed a combination of both quantitative and qualitative methods in order to explain the factors which influence students' decision to go for higher education.…”
Section: Methodsmentioning
confidence: 99%